Hallmarks in the Therapeutic Approach of Aortic Aneurysms: The Main Contributors - Karamanou, Marianna; Protogerou, Athanase; Siasos, Gerasimos; Chatziioannou, Achilleas; Androutsos, George (Current Pharmaceutical Design, 2015)
Deriving from the Greek word for “widening”, aneurysms have been a well known entity since antiquity. In the 2nd century AD, Antyllos, the Greek born surgeon who practiced in Rome, described a method for aneurysms’ surgical removal that remained a standard procedure till the 19th century. In 18th century John Hunter proposed a limb saving operation method for treating peripheral aneurysms paving thus the way for the modern surgery of aneurysms and Rudolph Matas, carried out the first aneurysmorrhaphy. During the 20th century two eminent surgeons laid the foundations of vascular surgery: Charles Dubost, who utilized the first homograft for aneurysm repair and Michael DeBakey, who performed the first radical treatment of a thoracic aneurysm.
Keywords: Dacron graft